The Association between Glycemic Control with Oxidant Status Parameters in Type 2 Diabetic Patients: Glycemic Control and Oxidant Status Parameters - Saberi-Karimian, Maryam; Norouzy, Abdolreza (Acta Biomedica Atenei Parmensis, 2021)
Purpose: Glycemic control is important in order to avoid LDLs increased susceptibility to oxidation in diabetic patients. This study assess the relationship between diabetes control with serum prooxidant-antioxidant balance (PAB), oxidized LDL cholesterol (oxLDLc), homocysteine and vitamin D levels in patients with type 2 diabetes. Material and methods: This was a cross-sectional study on three groups including 80 subjects as well (WGC) and poor (PGC) glycemic control and 40 healthy subjects. Presence of nephropathy and retinopathy were determined using IDF criteria. HbA1c level was determined with columnar chromatography using BioSystems kit. Serum PAB, homocysteine, oxLDLc and vitamin D levels were measured by the standard tests. Results: There was a significant association between PAB with PGC (P< 0.001), diabetic retinopathy (P< 0.01) and nephropathy (P< 0.01) in type 2 diabetic patients. Moreover, the results showed that vitamin D serum levels was significantly lower in PGC patients (P< 0.01), and diabetic patients with retinopathy (P< 0.01). Multiple linear regression analysis revealed that the vitamin D deficiency can predict the HbA1c variations by 77.7% (β=- 0.775) in subjects with type 2 diabetes mellitus (P<0.001). Conclusions: There was a significant association between prooxidant-antioxidant balance and vitamin D serum levels with diabetic complications.